Manual Electrode Array Insertion Through a Robot-Assisted Minimal Invasive Cochleostomy: Feasibility and Comparison of Two Different Electrode Array Subtypes. Issue 6 (July 2015) - Venail, Frederic; Bell, Brett; Akkari, Mohamed; Wimmer, Wilhelm; Williamson, Tom; Gerber, Nicolas; Gavaghan, Kate; Canovas, Francois; Weber, Stefan; Caversaccio, Marco; Uziel, Alain
Abstract : Hypothesis: To evaluate the feasibility and the results of insertion of two types of electrode arrays in a robotically assisted surgical approach. Background: Recent publications demonstrated that robot-assisted surgery allows the implantation of free-fitting electrode arrays through a cochleostomy drilled via a narrow bony tunnel (DCA). We investigated if electrode arrays from different manufacturers could be used with this approach. Methods: Cone-beam CT imaging was performed on fivecadaveric heads after placement of fiducial screws. Relevant anatomical structures were segmented and the DCA trajectory, including the position of the cochleostomy, was defined to target the center of the scala tympani while reducing the risk of lesions to the facial nerve. Med-El Flex 28 and Cochlear CI422 electrodes were implanted on both sides, and their position was verified by cone-beam CT. Finally, temporal bones were dissected to assess the occurrence of damage to anatomical structures during DCA drilling. Results: The cochleostomy site was directed in the scala tympani in 9 of 10 cases. The insertion of electrode arrays was successful in 19 of 20 attempts. No facial nerve damage was observed. The average difference between the planned and the postoperative trajectory was 0.17 ± 0.19 mm at the level of the facial nerve. The average depth of insertion was 305.5 ± 55.2 and 243 ± 32.1 degrees with Med-El and Cochlear arrays, respectively. Conclusions: Robot-assisted surgery is a reliable tool to allow cochlear implantation through a cochleostomy. Technical solutions must be developed to improve the electrode array insertion using this approach. Abstract : Supplemental digital content is available in the text.